A cross-biome analysis of Cedrela fissilis Vell: Growth, age, and diameter class transitions - Lidio López; Cláudia Fontana (Trees, Forests and People)
The measurement of tree-rings of Cedrela fissilis was used to determine the variability of diametric and basal growth across three sites located in the Cerrado biome in Bolivia and one in the Atlantic Forest, Santa Catarina, Brazil. The growth variability in growth is particularly pronounced among sites when trees have smaller diameters and during the initial 50 years of their lives. Initial growth rates are generally higher in those sites recovered from agricultural to forest lands or highly impacted forests than those growing in well-established forests. Optimal basal growth for the four sites occurs between 60 and 80 years old. The estimated times required for C. fissilis trees to grow from a given diameter to the next one are longer at the JBA and LCH sites. Under optimal conditions, this species requires 12 years to grow from 1 to 10 cm in diameter at STA. Conversely, when growth is slower and the diametric size is larger, they need about 23 years to grow from 31 to 40 cm. The JBA and LCH sites require >100 years to reach diameters of 50 cm, the AAI (Average Annual Increase) of 0.83 cm for diameters of 1–10 cm corresponds to STA, while in this same diametric class, the lowest of 0.36 cm corresponds to LCH. In diametric sizes of 41–50 cm, the highest growth of 0.47 cm corresponds to INP and the lowest of 0.31 cm to STA. The average time necessary to grow diameters of 10 cm, the lowest is 19.2 years corresponding to the site of INP and LCH requires an average of 22.4 years.The age of the trees required to be part of the deck, in order to achieve optimal growth, is dependent on to site-specific factors, such as light and soil nutrients. By combining this information with data on passage times, it is possible to project forest management based on an understanding of the specific events in which trees of this species change their growth dynamics within a given site or biome.